THE PROBLEMS OF DISPUTE SETTLEMENT IN COURT IN IN THE FIELD OF OCCUPATIONAL MEDICINE, RELATED TO THE SPECIFICS OF THESE LEGAL RELATIONS - Ксения Валерьевна Гаврылышена; Виктор Андреевич Семенихин; Сергей Николаевич Филимонов; Елена Владимировна Часовских (Медицина в Кузбассе)
The high prevalence of occupational diseases among workers of the Kemerovo region engaged in production with harmful factors, especially in the coal mining industry, leads to a high number of appeals to Occupational Pathology Centers, and also generates a large number of appeals to judicial authorities in case of refusal due to the disease with the profession. Also in recent years, cases of complaints to judicial authorities on issues of disagreement with the results of the examination of professional suitability have become more frequent. The issues of dispute resolution in connection with obligations arising from harm to the life and health of citizens are within the competence of courts of general jurisdiction.